2003
DOI: 10.1046/j.1365-246x.2003.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Validating Earth and ocean tide models using tidal gravity measurements

Abstract: SUMMARY O1 and M2 observations from well‐calibrated spring gravimeters and superconducting gravimeters from the Global Geodynamics Project (GGP) are used to test models of the Earth's body tide and 10 ocean tide models. It is shown that some of the ocean tide models give anomalous results in various parts of the world. For example, the Schwiderski ocean tide model gives discrepancies in several areas and the FES series of ocean tide models have problems in the western Pacific (China, Japan and Australia). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 41 publications
5
76
0
Order By: Relevance
“…Continuous gravity observations (Baker and Bos 2003;Llubes and Mazzega 1997) , using a different spatial sampling to this study, have previously established that there is not a single global ocean tide model that fits observations equally well globally and that models perform differently in different regions. Whilst we have shown that GPS is not capable of distinguishing between the five models in an overall global comparison of OTLD, there are certain sites and constituents where GPS can separate the models at a 95% confidence level.…”
Section: Spatial Variationsmentioning
confidence: 89%
See 2 more Smart Citations
“…Continuous gravity observations (Baker and Bos 2003;Llubes and Mazzega 1997) , using a different spatial sampling to this study, have previously established that there is not a single global ocean tide model that fits observations equally well globally and that models perform differently in different regions. Whilst we have shown that GPS is not capable of distinguishing between the five models in an overall global comparison of OTLD, there are certain sites and constituents where GPS can separate the models at a 95% confidence level.…”
Section: Spatial Variationsmentioning
confidence: 89%
“…Baker and Bos (2003) have demonstrated that such gravity measurements were of sufficient accuracy to distinguish between different ocean tide models.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gravity effect due to ocean tide loading (OTL) is needed for correcting gravity measurements, assessing ocean tide models and validating the theory of tidal loading (Sato and Hanada 1984;Shum et al 1997;Yamamoto et al 2001;Baker and Bos 2003;Boy et al 2004;Neumeyer et al 2005;Hwang et al 2009). There are many OTL programs in the earth science community which serve such needs, e.g., GOTIC (Sato and Hanada 1984), OLFG/OL-MPP (Scherneck 1991), SPOTL (Agnew 1996), NLOADF (Agnew 1997), CARGA (Bos and Baker 2005), GOTIC2 (Matsumoto et al 2001) and g7.0 (g7 User's Manual 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental differences between O1 and M2 are also implied by the work of Baker and Bos [2003], who found that tidal loading corrections to gravity data using a wide variety of ocean tide models led to more consistent and diminished residuals at the O1 than at the M2 frequency.…”
Section: Discussionmentioning
confidence: 81%